2014
DOI: 10.1111/acem.12548
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Injury With Substance Use Disorder Among Women of Reproductive Age: An Opportunity to Address a Major Contributor to Recurrent Preventable Emergency Department Visits?

Abstract: Objectives: Substance use disorder (SUD) among women of reproductive age is a complex public health problem affecting a diverse spectrum of women and their families, with potential consequences across generations. The goals of this study were 1) to describe and compare the prevalence of patterns of injury requiring emergency department (ED) visits among SUD-positive and SUD-negative women and 2) among SUD-positive women, to investigate the association of specific categories of injury with type of substance use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Prior research has been limited to small samples and specific treatments; this finding is the first demonstration, to our knowledge, of a positive association with treatment on a population basis. In other prior related studies, Bernstein et al (2014 & 2015) showed that among all MA SUD women aged 15–49 years, SUD treatment was associated with decreased subsequent ED visits, injuries, and hospitalizations within one year of treatment.…”
Section: Discussionmentioning
confidence: 80%
“…Prior research has been limited to small samples and specific treatments; this finding is the first demonstration, to our knowledge, of a positive association with treatment on a population basis. In other prior related studies, Bernstein et al (2014 & 2015) showed that among all MA SUD women aged 15–49 years, SUD treatment was associated with decreased subsequent ED visits, injuries, and hospitalizations within one year of treatment.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, providing appropriate information to patients regarding their medications and improved awareness of drug and substances abuse-associated dangers, especially illicit drugs, indiscriminate smoking, and alcohol consumption, will go a long way towards curbing drug-related ED visits. 65…”
Section: Resultsmentioning
confidence: 99%
“…16 Women who received treatment based on positive drug/alcohol screening results have been shown to subsequently have fewer future ED visits, injuries and hospitalization. 4 , 17 …”
Section: Discussionmentioning
confidence: 99%